From Tradition to Global Trade: Cultural Value Transformation in Seaweed Farming Communities of Laikang Village, Takalar. - Ikbal P; Pawennari Hijjang; Muhammad Fadland (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2026)
This study examines the transformation of cultural values within seaweed farming communities in Laikang Village, Mangarabombang District, Takalar Regency, as reflected in the traditional practice of Ma’ Bettang. In line with the theme From Tradition to Global Trade: Cultural Value Transformation in Seaweed Farming Communities of Laikang Village, Takalar this research explores how a local cultural tradition that once functioned as a symbolic and spiritual marker within the community is increasingly shaped by the dynamics of global trade and market expansion. Traditionally, Ma’ Bettang served not only as a ritual marker signaling the beginning of seaweed cultivation but also as a collective cultural symbol representing the spiritual, ecological, and social relationships between coastal communities and the sea. Using an ethnographic approach and drawing on Clifford Geertz’s theory of symbolic interpretation alongside Peter L. Berger and Thomas Luckmann’s theory of the social construction of identity, this study investigates the meanings embedded in the tradition, the cultural values transmitted through it, and the processes of transformation that occur as global economic forces penetrate local livelihoods. Data were collected through participant observation, in-depth interviews with community members involved in seaweed farming, and field documentation conducted during four days of field research. This transformation reflects a broader process in which local traditions are negotiated, adapted, and sometimes commodified under the influence of globalization. This study argues that the transformation from tradition to global trade does not necessarily eliminate cultural practices but rather reshapes their meanings within new socio-economic contexts. This ethnographic research contributes to discussions on maritime cultural studies, the anthropology of globalization, and the cultural transformation of coastal communities engaged in seaweed farming